2020
DOI: 10.5937/nabepo25-27062
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of body mass index based on self-report data among law enforcement cadets

Abstract: BACKGROUND - Height and body mass are often self-reported by study participants. However, the accuracy of this data compared to measured values is limited in tactical trainee populations. This study's purpose was to compare the accuracy of self-reported height and body mass to measured values within a US law enforcement cadet population, and determine how these estimations affected BMI classifications. METHODS - Self-reported and measured body height and body mass for twenty-six (n = 26) male and female cadets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Body height and body mass data were self-reported after previously described procedures (8,12). Dawes et al (8) showed that self-reported body height and body mass were accurate when compared with measured data, whereas Johnson et al (12) found significant but trivial differences between the reported and measured body mass (1.2%) and body height (0.8%) of police officers. Although measuring the anthropometric characteristics and body composition with more accurate tools would be beneficial, because of time constraints posed by the students' lecture schedule, the researchers were not able to perform these measurements.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body height and body mass data were self-reported after previously described procedures (8,12). Dawes et al (8) showed that self-reported body height and body mass were accurate when compared with measured data, whereas Johnson et al (12) found significant but trivial differences between the reported and measured body mass (1.2%) and body height (0.8%) of police officers. Although measuring the anthropometric characteristics and body composition with more accurate tools would be beneficial, because of time constraints posed by the students' lecture schedule, the researchers were not able to perform these measurements.…”
Section: Subjectsmentioning
confidence: 99%
“…The mean relative load produced by the load 10 kg condition was 11.9 and 16.3% in male and female students, respectively. Body height and body mass data were self-reported after previously described procedures (8,12). Dawes et al (8) showed that self-reported body height and body mass were accurate when compared with measured data, whereas Johnson et al (12) found significant but trivial differences between the reported and measured body mass (1.2%) and body height (0.8%) of police officers.…”
Section: Subjectsmentioning
confidence: 99%
“…The authors concluded that there was an obvious difference between police officers and the general population of workers in America regarding the professional aspect associated O N L I N E F I R S T with the prevalence for various diseases and health conditions, and that health risk factors were clearly higher in police work. Research on the characteristics of body composition, as part of a continuous system of information gathering, has been carried out in all police forces in the world (Hartley et al, 2011;Garbarino & Magnavita, 2015;Kukić & Dopsaj, 2016;Lockie et al, 2020;Johnson et al, 2020;Kukić et al, 2020;Vuković et al, 2020). In view of the previously mentioned research, there is a strong rationale for focusing on body composition in numerous studies on police personnel.…”
Section: Introductionmentioning
confidence: 99%